Museums: A visual anthropology - Stylianou-Lambert, Theopisti (My University, 2014)
Using diverse interdisciplinary literature from anthropology, sociology, museum studies and art history, Museums: A Visual Anthropology explores the complex histories and practices of collecting, archiving, exhibiting and displaying with a special emphasis on the visual.
Keywords: Museums; Museum studies; Visual anthropology